2014
DOI: 10.1068/p7692
|View full text |Cite
|
Sign up to set email alerts
|

Do Artists Use Linear Perspective to Depict Visual Space?

Abstract: The question of how to accurately depict visual space has fascinated artists, architects, scientists, and philosophers for hundreds of years. Many have argued that linear perspective, which is based on well-understood laws of optics and geometry, is the correct way to record visual space. Others have argued that linear perspective projections fail to account for important features of visual experience, and have proposed various curvilinear, subjective, and hyperbolic forms of perspective instead. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 50 publications
0
32
1
Order By: Relevance
“…This effect occurred in spite of participants’ knowledge about the physical properties of the peripherally viewed objects. These findings could help to explain why artists have often represented visual space using similar principles of peripheral diminution and compression ( Mather, 2015 ; Pepperell & Haertel, 2014 ). The picture changes somewhat when participants had to make judgments referring only to their peripheral vision under short time exposure.…”
Section: Discussionmentioning
confidence: 93%
“…This effect occurred in spite of participants’ knowledge about the physical properties of the peripherally viewed objects. These findings could help to explain why artists have often represented visual space using similar principles of peripheral diminution and compression ( Mather, 2015 ; Pepperell & Haertel, 2014 ). The picture changes somewhat when participants had to make judgments referring only to their peripheral vision under short time exposure.…”
Section: Discussionmentioning
confidence: 93%
“…Judgements are made about the portion of the visual field occupied by each perceived object, its location and shape, and these are recorded in the drawing. Having carried out this procedure many times in relation to different scenes we have found it consistently results an image in which the area of the scene being viewed in central or foveal vision is enlarged compared to how it would appear in an equivalent rectilinear or fisheye perspective projection ( Pepperell & Haertel, 2014 ; Pepperell, in press . See also Figure 4 ).…”
Section: Methodsmentioning
confidence: 90%
“…In a previous study we showed pictures created with this method represent visual space in a way that deviates consistently from the rules of linear perspective. Artists such as John Constable, Vincent van Gogh, and Paul Cézanne used a broadly similar approach when painting landscapes, as did a group of people with art training when drawing a still life ( Pepperell & Haertel, 2014 ). But to date no studies have been carried out to determine whether artistic depictions are superior to their geometrical perspective counterparts in terms of being able to accurately convey the visual space they depict.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative is more natural media (Smith et al 2016) and technologies that are modelled on human perception, cognition, awareness and proprioception, and take into account how our bodies interact with the environment, and how different sensory modalities interact with each other. FOVO (Field of View Opened) is a form of natural media that provides a more naturalistic and immersive form of imaging (Pepperell et al 2019) than is provided by conventional cameras and computer graphics systems, which universally rely on linear perspective, invented by artists during the Renaissance but long seen as ineffective for representing the full scope of human vision (Pepperell and Haertel 2014).…”
Section: Technology Presence and Healingmentioning
confidence: 99%